Effect of magnetization pretreatment of coal slime water flocculating sedimentation. Issue 12 (2nd December 2022) - Liao, Yinfei; Yang, Aosheng; An, Maoyan; Yang, Zhe; Cao, Yijun; Chen, Luojian; Ren, Hourui
ABSTRACT: Sedimentation of coal slime water (CSW) is an important process in coal processing plants. However, CSW is difficult to settle because of its high content of clay minerals and fine particles. In this paper, the effect of magnetization pretreatment on CSW flocculating sedimentation is investigated. The mechanisms of magnetization pretreatment were studied by measuring CSW's viscosity and zeta potential and calculating particle's hydration film thickness using Einstein's viscosity equation. The results show that the CSW flocculating sedimentation is enhanced by magnetization pretreatment. The optimum dosage of polyacrylamide was 6.0 mg/L and the best magnetic field strength and magnetization time was 0.3 T and 3 min, respectively. As the settling velocity was increased, the turbidity of the supernatant was reduced by magnetization pretreatment. Moreover, after magnetization pretreatment, the absolute value of the zeta potential and the viscosity were reduced, and the hydrated film thickness of coal particles was decreased from 305 nm to 155 nm. Magnetization pretreatment decreased the settling resistance and reduced the electrostatic repulsion and hydration forces between coal particles, thus promoting CSW flocculating sedimentation. It is demonstrated that magnetization pretreatment introduces a new path improve CSW settlement.